2017
DOI: 10.1002/jmri.25719
|View full text |Cite
|
Sign up to set email alerts
|

Valve mediated hemodynamics and their association with distal ascending aortic diameter in bicuspid aortic valve subjects

Abstract: Purpose Valve mediated hemodynamics have been postulated to contribute to pathology of the ascending aorta (AAo). The objective of this study is to assess the association of aortic valve morphology and hemodynamics with downstream AAo size in subjects with bicuspid aortic valve (BAV) disease. Materials and Methods Four‐dimensional flow MRI at 1.5 or 3 Tesla was used to evaluate the hemodynamics in the proximal AAo of 52 subjects: size‐matched controls with tricuspid aortic valves (n = 24, mid ascending aorta [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 26 publications
1
12
0
1
Order By: Relevance
“…This study shows that children and adolescent TGA patients after ASO have an eccentric systolic flow in the ascending aorta: regions of most prominent flow eccentricity were detected at the level of the neo‐aortic root and STJ. Consistent with the results of studies in patients with a bicuspid aortic valve, we found a close linear relationship between aortic dimensions and the normalized FD. In one of these studies, systolic FD was correlated with future ascending aortic growth in patients with bicuspid valve anatomy .…”
Section: Discussionsupporting
confidence: 91%
“…This study shows that children and adolescent TGA patients after ASO have an eccentric systolic flow in the ascending aorta: regions of most prominent flow eccentricity were detected at the level of the neo‐aortic root and STJ. Consistent with the results of studies in patients with a bicuspid aortic valve, we found a close linear relationship between aortic dimensions and the normalized FD. In one of these studies, systolic FD was correlated with future ascending aortic growth in patients with bicuspid valve anatomy .…”
Section: Discussionsupporting
confidence: 91%
“…There is extensive evidence that blood flow and shear stress in the tubular ascending aorta are markedly altered by a BAV, even in the absence of significant flow obstruction (Entezari et al, 2014 ; Garcia et al, 2016 ; Cao et al, 2017 ; Raghav et al, 2017 ; Shan et al, 2017 ; Figure 9 ). However, fused-leaflet morphology is not a sole determinant of helicity of blood flow or region of maximal wall stress in the tubular ascending aorta (Raghav et al, 2017 ; Shan et al, 2017 ), as age and clinical characteristics are important (Burris et al, 2016 ; Girdauskas et al, 2016b ; van Ooij et al, 2016 ; Shan et al, 2017 ).…”
Section: Hemodynamic and Genetic Mechanisms Of Bav-related Aortopathymentioning
confidence: 99%
“…Aortic dimension has been the most used marker of aortic dissection risk, yet it provides little prognostic information over the clinically important range of 40–55 mm (2010 ACCF/AHA/AATS/ACR/ASA/SCA/SCAI/SIR/STS/SVM Guidelines For the Diagnosis and Management of Patients with Thoracic Aortic Disease Representative, Erbel et al, 2014 ; 2010 ACCF/AHA/AATS/ACR/ASA/SCA/SCAI/SIR/STS/SVM Guidelines For the Diagnosis and Management of Patients with Thoracic Aortic Disease Representative Members et al, 2016 ), while the majority of aortic dissections occur at dimensions less than these (Pape et al, 2007 ). This limitation has led to other approaches such as examining morphometry (Biaggi et al, 2009 ; Habchi et al, 2017 ), hemodynamic factors (Atkins et al, 2016 ; DeCampli, 2017 ; Raghav et al, 2017 ), the position and shape of the aneurysm (Schaefer et al, 2008 ; Della Corte et al, 2014b ), aortic growth rate (Elefteriades and Farkas, 2010 ), and aortic distensibility parameters (Benedik et al, 2013 ). To date, observed population-based associations are weak and are unlikely to provide any predictive value for the individual patient.…”
Section: Is There a Biomarker For Aortic Dissection?mentioning
confidence: 99%
“…A recent study reported that valve-mediated hemodynamics are even correlated with the distal ascending aorta [67]. Fourdimensional flow MRI can identify the eccentric jet flow in patients with BAV and may help stratify the risk for development of ascending aortic aneurysms and aortic dissection.…”
Section: Bicuspid Aortic Valvementioning
confidence: 99%